Answer:
Equation 1:
![x+y =23.](https://img.qammunity.org/2020/formulas/mathematics/high-school/yhwfjedbodiori0j8jrpggcwvqwi5ibeal.png)
Equation 2 :
![x-y =3.](https://img.qammunity.org/2020/formulas/mathematics/high-school/pdkt83om40s3fzxxtuexwm1vfps65f5d9t.png)
1st number: 13
2nd number: 10
Explanation:
Let the first number be x;
x = first number
Let the second number be y;
y = second number
Now Given, Two numbers add up to 23.
Hence the equation can be made as;
![x+y =23.](https://img.qammunity.org/2020/formulas/mathematics/high-school/yhwfjedbodiori0j8jrpggcwvqwi5ibeal.png)
Equation 1:
![x+y =23.](https://img.qammunity.org/2020/formulas/mathematics/high-school/yhwfjedbodiori0j8jrpggcwvqwi5ibeal.png)
Also Given, 7 times the difference of the two numbers is 21.
Hence the equation can be made as;
![7(x-y) =21](https://img.qammunity.org/2020/formulas/mathematics/high-school/kyhb4xy1bjhl7b0kbgi7o0qcww5bcn4npi.png)
Dividing 7 on both side we get;
![(7(x-y))/(7) =(21)/(7)\\\\x-y = 3](https://img.qammunity.org/2020/formulas/mathematics/high-school/xtb1w9s8i3nwpjzm64a3zb3lparllkdbp1.png)
Equation 2 :
![x-y =3.](https://img.qammunity.org/2020/formulas/mathematics/high-school/pdkt83om40s3fzxxtuexwm1vfps65f5d9t.png)
Now we will solve the system of equations we get;
We will add equation 1 and equation 2 we get;
![(x+y)+(x-y) =23+3\\x+y+x-y=26\\2x=26\\x = (26)/(2)=13](https://img.qammunity.org/2020/formulas/mathematics/high-school/v2rzq8xkavzdmzzywq9qs466jkrku21jtw.png)
1st number: 13
Now Substituting the value of x in equation 1 we get;
![x+y=23\\13+y=23\\y=23-13\\y=10](https://img.qammunity.org/2020/formulas/mathematics/high-school/i4m4muv2afk4j37bluhovdnu3ob4hlghc2.png)
2nd number: 10
Hence Final Answer is.
Equation 1:
![x+y =23.](https://img.qammunity.org/2020/formulas/mathematics/high-school/yhwfjedbodiori0j8jrpggcwvqwi5ibeal.png)
Equation 2 :
![x-y =3.](https://img.qammunity.org/2020/formulas/mathematics/high-school/pdkt83om40s3fzxxtuexwm1vfps65f5d9t.png)
1st number: 13
2nd number: 10